2006
DOI: 10.1253/circj.70.662
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Adverse Effects During Bepridil Administration for Atrial Fibrillation and Flutter

Abstract: Background Bepridil hydrochloride (Bpd) has attracted attention as an effective drug for atrial fibrillation (AF) and atrial flutter (AFL). However, serious adverse effects, including torsade de pointes (Tdp), have been reported. Methods and Results Adverse effects of Bpd requiring discontinuation of treatment were evaluated. Bpd was administered to 459 patients (361 males, 63±12 years old) comprising 378 AF and 81 AFL cases. Mean left ventricular ejection fraction and atrial dimension (LAD) were 66±11% and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 14 publications
(25 reference statements)
1
39
0
Order By: Relevance
“…25, 26 In the present study, we observed ventricular arrhythmic events with considerable incidence, ie, 6/113 patients, so prediction of these events should be an extremely important issue during bepridil therapy. However, this incidence does not directly indicate the prevalence of ventricular arrhythmic event during bepridil therapy because 1 patient with arrhythmic episode was transferred to our hospital due to the event.…”
Section: Prediction Of Ventricular Arrhythmic Events During Bepridil mentioning
confidence: 54%
“…25, 26 In the present study, we observed ventricular arrhythmic events with considerable incidence, ie, 6/113 patients, so prediction of these events should be an extremely important issue during bepridil therapy. However, this incidence does not directly indicate the prevalence of ventricular arrhythmic event during bepridil therapy because 1 patient with arrhythmic episode was transferred to our hospital due to the event.…”
Section: Prediction Of Ventricular Arrhythmic Events During Bepridil mentioning
confidence: 54%
“…Bepridil is still available in Japan at an appropriately lower dose (100-200 mg/day) and the evidence regarding efficacy and adverse effects, including TdP, has accumulated. Yasuda et al investigated the incidence of side effects in a total of 459 patients treated with bepridil 13) . QT prolongation was observed in 13 cases (2.8%) and 4 cases (0.9%) among them developed TdP.…”
Section: Adverse Effects Of Bepridilmentioning
confidence: 99%
“…Bepridil-induced TdP has been reported to be more prevalent in patients with structural heart disease and in the presence of hypokalemia or marked bradycardia, conditions known to reduce the repolarization reserve and increase the spatial heterogeneity of ventricular repolarization. [10][11][12]14,45,46 Under such pathologic conditions, bepridil would further enhance the heterogeneity of ventricular repolarization to a critical level for the induction of TdP. Unraveling the spatial and dynamic modification of the action potential properties by bepridil in human hearts under such pathological conditions will be a subject for further investigation.…”
Section: Study Limitationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Despite its usefulness for the treatment of AF, there remains some concern about the drug-induced polymorphic ventricular tachycardia, known as torsades de pointes (TdP), in association with QT prolongation. [10][11][12][13] The QT prolongation is attributable to the blockade of several K + outward currents, including the rapidly and slowly activating delayed rectifier K + currents (IKr and IKs). [2][3][4][5] Spatially inhomogeneous prolongation of ventricular action potential duration (APD) through an inhibition of IKr (with or without concomitant inhibition of IKs) can provide a substrate for functional reentry leading to TdP.…”
mentioning
confidence: 99%